Transcriptomic Signature of Human Embryonic Thyroid Reveals Transition From Differentiation to Functional Maturation - Dom, Geneviève; Dmitriev, Petr; Lambot, Marie-Alexandra; Van Vliet, Guy; Glinoer, Daniel; Libert, Frédérick; Lefort, Anne; Dumont, Jacques E.; Maenhaut, Carine (Frontiers in Cell and Developmental Biology, 2021)
The human thyroid gland acquires a differentiation program as early as week 3-4 of embryonic development. The onset of functional differentiation, which manifests by the appearance of colloid in thyroid follicles, takes place during gestation weeks 10-11. By 12-13 weeks functional differentiation is accomplished and the thyroid is capable of producing thyroid hormones although at a low level. During maturation, thyroid hormones yield increases and physiological mechanisms of thyroid hormone synthesis regulation are established. In the present work we traced the process of thyroid functional differentiation and maturation in the course of human development by performing transcriptomic analysis of human thyroids covering the period of gestation weeks 7-11 and comparing it to adult human thyroid. We obtained specific transcriptomic signatures of embryonic and adult human thyroids by comparing them to non-thyroid tissues from human embryos and adults. We defined a non TSH (thyroid stimulating hormone) dependent transition from differentiation to maturation of thyroid. The study also sought to shed light on possible factors that could replace TSH, which is absent in this window of gestational age, to trigger transition to the emergence of thyroid function. We propose a list of possible genes that may also be involved in abnormalities in thyroid differentiation and/or maturation, hence leading to congenital hypothyroidism. To our knowledge, this study represent the first transcriptomic analysis of human embryonic thyroid and its comparison to adult thyroid.